The Effect Of Seed Size Against The Growth Of Seedlings Of Cocoa (Theobrama Cacao L.): Pengaruh Ukuran Benih Terhadap Pertumbuhan Bibit Kakao (Theobrama cacao L.) - wahyudi wahyudi (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2019)
The purpose of this study was to determine the effect of seed size on the growth of cacao seedlings (Theobrama cacao L.). The purpose of this study was to determine the effect of seed size on the growth of cacao seedlings (Theobrama cacao L). The design used in this study is Non Factorial Randomized Group Design (RBD). That is the size of the cocoa seed (S) consists of 3 levels of treatment, each treatment was repeated as many as 5 replications so that 15 units of experiment were obtained. Each experimental unit consists of 4 plants, 3 of which are used as sample plants. The treatment is as follows: S1: Size of weight> 2 grams per seed. S2: Medium Size 1.4-1.6 grams per seed. S3: Small Size <1 gram per seed Observation data were statistically analyzed and continued with a further test of real honest difference at the 5% level. The parameters observed were: germination (%), plant height (cm), number of leaves (strands), root volume (ml), wet weight of plants (grams). Based on the results of this study it can be concluded that the treatment of cocoa seed size affects plant height (29.50 cm) the best treatment S1, number of leaves (16.70 strands) best treatment S1, root volume (7.40 ml) best treatment S1, weight wet plant (37.10 grams) best treatment S1.